PREDIKSI TEKANAN UAP DAN VOLUME MOLAR SENYAWA HIDROKARBON DENGAN PERSAMAAN TINGKAT KEADAAN - Ratnawati Ratnawati; Aryadi Suwono; H.M Samudro (Mesin, 1996)
Vapor pressures and saturated liquid molar volumes of hydrocarbons up to n-C16 were predicted using equations of states. The equations of states used were Redlich-Kwong (RK), Mohsen Nia et al.-Redlich-Kwong (MRK), Saave-Redlich-Kwong (SRK), and Peng-Robinson (PR). The calculated values were compared to the experimental data extracted from various sources. The results indicated that PR eos was superior among the others.